Coleção de referência de silicofitólitos da flora do Sudoeste do Paraná: subsídios para estudos paleoambientais - Raitz, Edenilson (2012)
Phytoliths bodies are of amorphous silica (SiO2.nH20) produced during the vegetative cycle and plant death after the production can be incorporated into the soil/sediment, and may remain there for extended periods of time. For an analysis consistent fitolítica is necessary to compare the sets of phytoliths found in soil and the collections of references phytoliths extracted from existing plants. The problem is there is no reference collection available for the Southwest region of Paraná and in Brazil, so there is no possibility of comparisons difficult paleoenvironmental reconstructions through this proxy. In order to minimize the lack of information on the production of phytoliths by vegetation of Brazil was made a reference collection of phytoliths from phytophysionomies Mixed Ombrophylous Forest and grassland, both located in the Southwest of Paraná State. This collection consists of 30 families, 57 genera and 75 species. In the floristic survey of FOM Lauraceae, Myrtaceae, Poaceae, and Fabaceae Pteridaceae families have greater representation of species. The vegetation of the grassland had a high representation of Poaceae, Asterceae, Cyperaceae, and Lauraceae. It was found that the production of Late Gray (fraction that contains the phytoliths) decrease of herbaceous to woody phytophysionomies in both. Only two (Araucaria angustifolia and Rapanea gardneriana) of 71 species analyzed did not produce identifiable phytoliths in the leaves. The production of phytoliths in different strata varied in similar proportions in the FOM and the field, especially in stratum A, because the presence of grass species that contributed to high amount of morphotypes short-cells (bilobate, cross and saddle, rondel and conical) in two forest types. While the layers B, C, D and redundancy Epiphytes presented to each other for producing morphotypes blocky, tabular, globular, cylindric and irregular cells by species. The production of phytoliths in the FOM morphological differ in quantity significantly from conjuto produced by species of the grassland, since grasses produce more biomineralizations than eudicotyledonous. The analysis fitolítica the first 40 cm of soil under the FOM revealed a change in vegetation type, evolving from a opened vegetation to more closed forest (current). It was possible to deduce that this change has occurred as a result of past human action. Similar trend was found in the soil analysis of the grassland, that is, moved from grassland to grassland clean of this dirty again to grassland clean, change occurred due to the abandonment of the field and return of site anthropogenic activities. The degradation of two morphotypes differed in physiognomy. The morphotypes found in soil under the FOM showed the lowest degradation compared to the grassland. The set of two soils revealed significant patterns that differentiate the two forest types, showing that different vegetation units can be discriminated by the signatures phytolitic produced by them. These results reinforce the utility of using phytoliths as significant indicators to distinguish vegetation units dominated by field and/or forest, even in a short period of time, thus demonstrating the potential of phytoliths analysis for paleoecological reconstruction in southern Brazil.